The Making of Islamic Political Tradition in the Malay World - Jajat Burhanudin (Studia Islamika, 2001)
With regard to the word "Islamic" in the title of this study, "The Making of the Islamic Political Tradition", it might be significant to take the above quotation into consideration. In the Malay tradition, what the people say about themselves seems to support the argument which is revealed in the sentences quoted. One of the most well-known Malay proverbs runs as follows: "to convert to Islam is to become a Malay". This proverb obviously expresses the feelings of the Malay people who identify themselves with Islam. Islam is acknowledged as having constituted a significant part of Malay society; Islam is regarded as the source of its cultural identity. Thus, if what is conceived of as being Islamic as such is accepted, perhaps there is no reason to wonder how "Islamic" Malay society is; and there is a solid validation for taking the sentence quoted as the argument for this study.DOI: 10.15408/sdi.v8i2.687